The effectiveness of Diabetes Self-Management Education (DSME) with self-acceptance and self-care for diabetes mellitus patients - Elis Anggeria; Rahmaini Fitri Harahap; Kristina L Silalahi; Parida Hanum; Verawaty Fitrinelda Silaban (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Diabetes mellitus is a complex group of chronic diseases associated with hyperglycemia, resultingin impaired insulin secretion and other organs. Patients with type 2 diabetes mellitus will experience changes inthemselves. Each individual responds and has a different perception of dealing with these changes. Providingeducation aims to increase knowledge and improve the patient’s ability in self-care so that health problems areresolved.Objectives: The study wants to know the effectiveness of Diabetes Self-Management Education (DSME) onself-acceptance and self-care of Type II Diabetes Mellitus patients.Patient and Methods: A quasi-experimental design was used through one group pre-test and post-test design. Thetotal population is 25 people, with a saturated sampling technique, and a sample of 25 people. Data analysis useda non-parametric statistical test, namely the Wilcoxon Signed Rank Test.Results: The majority of patients with Diabetes Mellitus had good self-acceptance, and the majority of patients’self-care was found to be good (p=0.000).Conclusions: The resulting study is the effectiveness of DSME on patient self-acceptance and self-care.Recommendations: The DSME program requires involvement in glucose monitoring by health professionals.Providing education to patients effectively provides psychological support and patient self-care.